Mucoepidermoid Carcinoma of the Hard Palate in a Young Patient - Martins, Thiago Henrique; Bonardi, João Paulo; Stabile, Glaykon Alex Vitti; Ito, Fabio Augusto; Pereira-Stabile, Cecilia Luiz; Hochuli-Vieira, Eduardo (My University, 2016)
Carcinomas of salivary glands are rare and can affect major or minor salivary glands. Among them, the mucoepidermoid carcinoma is the most prevalent and its occurrence in the first 2 decades of life is highly unusual. Their common clinical aspect to different diseases is a challenge in diagnosis. The objective of this work is to elucidate the diagnosis of lesion in the hard palate of an adolescent patient, brown-skinned, male, forwarded to the oral surgery department at the State University of Londrina. Initially, he complained about a progressive swelling in the last 60 days. Through computed tomography scan, it was noted intraosseous involvement in the maxilla involving dental apex of the elements 13, 14, 15, right maxillary sinus extending to piriform sinus. Proceeding with clinical examination, followed by biopsy, histology, and immunohistochemical analysis, we established the diagnosis of mucoepidermoid carcinoma. After verification, the patient was sent to the referenced service to start cancer treatment.